2009
DOI: 10.1677/erc-09-0086
|View full text |Cite
|
Sign up to set email alerts
|

Genomic actions of estrogen receptor α: what are the targets and how are they regulated?

Abstract: The estrogen receptor a (ERa) is a ligand-dependent transcription factor that regulates a large number of genes in many different target tissues and is important in the development and progression of breast cancer. ERa-mediated transcription is a complex process regulated at many different levels. The interplay between ligand, receptor, DNA sequence, cofactors, chromatin context, and post-translational modifications culminates in transcriptional regulation by ERa. Recent technological advances have allowed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 126 publications
(99 reference statements)
2
120
0
8
Order By: Relevance
“…Oestradiol exerts its effects after binding to oestrogen receptors alpha (ERa) and ERb (Kim & Levin 2006, Madak-Erdogan et al 2008, Levin 2009, 2014b, Welboren et al 2009, Chambliss et al 2010, SchultzNorton et al 2011, Filardo & Thomas 2012, Arnal et al 2013, Hamilton et al 2014, Magnani & Lupien 2014. The predominant actions are mediated through the direct binding of the receptor to oestrogen response elements (EREs) in the nucleus and the initiation of transcription or by tethering to other transcription factors, such as AP1 and SP1, with DNA binding to their respective response elements.…”
Section: Molecular Mechanisms Of Action Of Oestrogensmentioning
confidence: 99%
“…Oestradiol exerts its effects after binding to oestrogen receptors alpha (ERa) and ERb (Kim & Levin 2006, Madak-Erdogan et al 2008, Levin 2009, 2014b, Welboren et al 2009, Chambliss et al 2010, SchultzNorton et al 2011, Filardo & Thomas 2012, Arnal et al 2013, Hamilton et al 2014, Magnani & Lupien 2014. The predominant actions are mediated through the direct binding of the receptor to oestrogen response elements (EREs) in the nucleus and the initiation of transcription or by tethering to other transcription factors, such as AP1 and SP1, with DNA binding to their respective response elements.…”
Section: Molecular Mechanisms Of Action Of Oestrogensmentioning
confidence: 99%
“…Welboren et al used ChIP-seq technology to explore ERBS and binding sites for RNA polymerase II in the MCF-7 genome in response to estradiol (E2) and antiestrogen, tamoxifen, or fulvestrant [66] . They identified the 10 205 E2-regulated ERBSs in MCF-7 cells and showed that tamoxifen and fulvestrant partially decrease the binding of ERα and RNA polymerase II around the E2-upregulated genes [66,67] . To examine the role of FOXA1 in ERα binding, Hurtado et al performed ChIPseq analysis of ER binding sites in MCF-7 cells in which FOXA1 was silenced with short interfering RNAs (siRNAs) [68] .…”
Section: Identification Of Estrogen-responsive Genes Using Highthrougmentioning
confidence: 99%
“…After proving that estrogens (17-β estradiol and genistein) increase both the number and sizes of tertiary tumorspheres as well as the level of proliferation marker PCNA, we demonstrated that both the hormones markedly increase PI-9 level in tumorspheres, suggesting their involvement in PI-9 upregulation. Estrogens are known to regulate different cellular processes stimulating both genomic and non-genomic pathways (3)(4)(5)(6)(7)(8). The classical mechanism of estrogen action involves the binding of the hormones to specific nuclear receptors (ERα66, its splice variant ERα46, and the closely related estrogen receptor ERβ) (7,8) which bind to estrogen responsive elements (EREs) located in the promoter of target genes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75% of BC cases is characterized by the presence of hormone receptors (ERs) whose expression is considered an important prognostic and therapeutic indicator (2)(3)(4). ERs are nuclear receptors that regulate the transcription of estrogen-responsive genes in target cells after ligand binding and dimerization (5,6).…”
Section: Introductionmentioning
confidence: 99%